The Industries Cooperation Of Information Technology Vocational High School - Kirya Mateeke Moses (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: The purpose of this study was to ascertain the linkage between vocational high school (SMK) cooperation with industries in the field of information technology in Malang City. This Qualitative research with descriptive approach was conducted in four public vocational high schools selected with a population of 48 people selected through simple random sampling method. Interview, observation methods together with school websites were used in data collection with school management and Information Technology teachers as the subject. The study findings showed that cooperation between vocational high schools with industries exists in several forms namely: internship for both teachers and students, on-job training, student assessment and recruitment as well as curriculum synchronization. The study also revealed some challenges facing vocational education.Key Words: vocational high school, cooperation, industries, information technologyAbstrak: Tujuan dari penelitian ini adalah untuk mengetahui keterkaitan antara kerja sama SMK dengan industri di bidang teknologi informasi di Kota Malang. Penelitian kualitatif dengan pendekatan deskriptif ini dilakukan di empat SMK Negeri yang dipilih dengan populasi 48 orang yang dipilih melalui metode simple random sampling. Wawancara dan metode observasi bersama pada website sekolah digunakan dalam pengumpulan data dengan manajemen sekolah dan guru Teknologi Informasi sebagai subjek-nya. Temuan penelitian ini menunjukkan bahwa kerja sama antara SMK dengan industri ada dalam beberapa bentuk, yaitu dalam bentuk kerjasama magang baik untuk guru dan siswa, pelatihan di tempat kerja, penilaian siswa, dan rekrutmen serta sinkronisasi kurikulum. Penelitian ini juga mengungkapkan beberapa tantangan yang dihadapi pendidikan kejuruan.Kata kunci: sekolah menengah kejuruan, kerjasama, industri, teknologi informasi